A Novel Specimen Produced by Additive Manufacturing for Pure Plane Strain Fatigue Crack Growth Studies - Jesus, Joel de (2021)
Fatigue crack growth is usually studied using C(T) or M(T) specimens with throughthickness cracks. The objective of the present study is to propose a cylindrical specimen with central crack, produced by additive manufacturing. This geometry allows to have pure plane strain state along the whole crack front, avoiding the complexities associated with corner points, crack shape, and variation of crack closure along crack front. Additionally, this geometry may be used to develop studies in vacuum, avoiding expensive vacuum equipment, since the air is not in contact with the crack front. Cylindrical specimens of Ti6Al4V titanium alloy were produced by Selective Laser Melting and tested at a stress ratio R = 0. Marking with overloads was the solution adopted to measure the length of the internal cracks. The fracture surfaces presented circular crack fronts and the da/dN-DK curves showed a great influence of atmosphere on fatigue crack growth. An average difference of 50% was found between the results in air and vacuum. Therefore, this geometry with internal crack is an interesting alternative to through-thickness geometries.